Envekadea metzeltinii sp. nov., a new diatom (Bacillariophyta) species from the subtropical karstic wetlands of the Florida Everglades, U.S.A. - Lee, Sylvia S.; Tobias, Franco A. C.; de Vijver, Bart Van (Phytotaxa, 2013)
Envekadea metzeltinii sp. nov. is described from periphyton assemblages in the subtropical karstic wetlands of the Florida Everglades, U.S.A. The morphology of the new diatom species is documented by light and scanning electron micrographs and discussed in detail, including comparisons with related species in the genera Envekadea, Caloneis, andNavicula. The new species is characterized by a linear valve outline, a sigmoid raphe course, broad variability in areola shapes and sizes, and two clearly raised axial costae. Apart from the type locality in Florida, the species was observed from similar wetlands in the Yucatan, Mexico. Notes on its ecology and distribution are added. Based on the morphology of the most similar species, Navicula palestinae, the latter is transferred to the genus Envekadea.